Experimental Behavior of Steel Slag in Concrete - Ram Charan, Medi; Sunil Pratap Reddy, S; Viqar Malik, Syed (International Journal of Computer Sciences and Engineering, 2025)
Global warming and environmental destruction has come forward as a major issue in the recent years. Started alarming in engineers mind, especially in civil engineers mind. Looking forward for finding out the solution of these issues and also the use of more and more environmental- friendly materials in every Industry particularly construction industry is a paramount importance. Civil engineers start thinking about concrete, which is more dominant product to be used by civil engineers to make it environmental friendly. One of its part is natural aggregates which are becoming increasingly scarce, their production and shipment is becoming difficult for us. Concrete mixture contains supplementary cementitious material and admixtures which forms part of the cementitious component. These materials are majority byproducts from other processes, out of all these materials one of the useful byproduct material is Steel slag. Steel slag is previously used as aggregate in hot mix asphalt surface applications, but needs to update for additional work to determine the feasibility of utilizing this industrial by-product more wisely as a replacement for both fine and coarse aggregates in a conventional concrete mixture. The primary aim of study was to evaluate the Fresh, Hardened, Expansive and Durability properties of concrete made with steel slag aggregates. This study presents result of experimental investigations carried out to evaluate effects of replacing aggregate (coarse and fine) with that of slag on various concrete properties. In the present study M35 grade of concrete each having two types of concrete mixes C: S: A, C: S: SS, C: SS: SS (SS is steel slag), and the properties were determined adopting conventional testing procedure. From these results of the study we can say that as the percentage of steel slag as replacement is increased (0% to 55%) the strength of concrete increases. After 55% replacement of Coarse aggregate as steel slag slight decrease in strength is observe, but still it is higher than 0% replacement without any adverse effect on the strength of concrete.